Association of Serum Kynurenine Levels and Neural Networks in Patients with First-Episode, Drug-Naïve Major Depression: A Source-Based Morphometry Study - Okamoto N (Dove Medical Press, 2020)
Naomichi Okamoto,1 Keita Watanabe,2 LeHoa Ngyuyen,1,3 Atsuko Ikenouchi,1 Taro Kishi,4 Nakao Iwata,4 Shingo Kakeda,5 Yukunori Korogi,6 Reiji Yoshimura1 1Department of Psychiatry, University of Occupational and Environmental Health, Kitakyushu, Japan; 2Open Innovation Institute, Kyoto University, Kyoto, Japan; 3School of Medicine and Pharmacy, Vietnam National University, Hanoi, Vietnam; 4Department of Psychiatry, Fujita Medical University, Toyoake, Japan; 5Department of Radiology, Graduate School of Medicine, Hirosaki University, Hirosaki, Japan; 6Department of Radiology, University of Occupational and Environmental Health, Kitakyushu, JapanCorrespondence: Reiji YoshimuraDepartment of Psychiatry, University of Occupational and Environmental Health, Kitakyushu, Fukuoka 8078555, JapanTel +81 936917253Email yoshi621@med.uoeh-u.ac.jpPurpose: The kynurenine (KYN) pathway can directly or indirectly influence cerebral volume and neural integrity in patients with major depression (MD). The aim of the present study was to investigate neural network systems and the KYN pathway in patients with first-episode, drug-naïve MD.Patients and Methods: Twenty right-handed drug-naïve patients, with MD diagnosed using the Diagnostic and Statistical Manual for Mental Disorders, Fourth Edition, Text Revision, Research Version, were included in this study. Magnetic resonance imaging scans and scores on the Hamilton Rating Scale for Depression were assessed, and serum sampling was performed prior to the start of pharmacological treatment. Image processing and data analysis were performed according to our recently published procedure. Serum metabolomes were measured in the cation and anion modes of CE-FTMS-based metabolome analysis.Results: We found that serum KYN levels were positively correlated with the Z-scores of the salience network but not with those of the central executive network or default mode network. No associations were observed between serum glutamate levels and the Z-score of any of the three networks.Conclusion: Our results indicate that serum KYN levels might affect the activity of the salience network in first-episode, drug-naïve patients with MD.Keywords: kynurenine, major depression, neural network, source-based morphometry